Calculation of the Relative Stopping Power of Protons and Alpha Particles In Water - Wafaa Nsaif Jasim Abuirqeba (Journal of Kufa-Physics, 2018)
n this research we studied and calculatedtherelative stopping power(RSP) of protons and alpha particles in water with energy (35-150)MeV by calculating the range of these particles in water and air, where the range of protons in water  calculated by usePSTARprogram and ASTARprogram to calculate the range of alpha particles in water for the same range of energy .The range of protons in air calculate by semi empirical equation while by using Bragg and Kleeman ruleincalculation the range of alpha particle in air.